2022
DOI: 10.1186/s12885-022-09823-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of computed tomography-derived body composition to determine the prognosis of patients with primary liver cancer treated with immune checkpoint inhibitors: a retrospective cohort study

Abstract: Background Immune checkpoint inhibitors (ICIs) have been used to successfully treat primary liver cancer (PLC); however, identifying modifiable patient factors associated with therapeutic benefits is challenging. Obesity is known to be associated with increased survival after ICI treatment; however, the relationship between body composition (muscle, fat) and outcomes is unclear. This study aimed to evaluate the association between sarcopenia and CT-derived fat content and the prognosis of ICIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
0
19
1
Order By: Relevance
“…NLR as a factor for recurrence or survival in HCC has been evaluated with various treatments, including surgical resection, radiofrequency ablation, liver transplantation, and transhepatic arterial chemoembolization [22-26]. Furthermore, Rich et al [23] have found that the mortality was significantly increased in patients with a baseline NLR <5 than in those with baseline NLR ≥5.…”
Section: Discussionmentioning
confidence: 99%
“…NLR as a factor for recurrence or survival in HCC has been evaluated with various treatments, including surgical resection, radiofrequency ablation, liver transplantation, and transhepatic arterial chemoembolization [22-26]. Furthermore, Rich et al [23] have found that the mortality was significantly increased in patients with a baseline NLR <5 than in those with baseline NLR ≥5.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been repeatedly associated with poor OS in cancer patients [52,54,61,62], which extends to ICI treatment outcomes. Cachexic gastric cancer patients previously treated with chemotherapy who received nivolumab had a significantly worse median OS (2.3 vs. 6.6 months, HR 2.65, 95% CI [1.28-5.49]) and time to treatment failure (1.8 vs. 2.6 months, HR 2.65, 95% CI [1.28-5.49]) compared to non-cachectic patients [61].…”
Section: Sarcopeniamentioning
confidence: 93%
“…Patients with a BMI of ≥25 had improved objective response rates (41.3% vs. 20.9%, p < 0.0001), a median PFS (11.7 vs. 3.7 months, HR 0.46, 95% CI [0.39-0.54]), and a median OS (26.6 vs. 6.6 months, HR 0.33, 95% CI [0.28-0.41]) compared to those with a BMI of <25 [53]. Other measures of adipose tissue, including the visceral adipose tissue index based on baseline CT imaging, have shown similarly positive associations in GI cancer patients [54].…”
Section: Body Mass Indexmentioning
confidence: 97%
“…Moreover, additional evidences on the role of changes of WAT in cancer have been obtained by retrospective studies conducted among gastrointestinal cancers and in hematological diseases [35–39,40 ▪ ,41–43]. Also, a systematic review including studies on COPD showed a link between changes in adiposity and cardiovascular diseases [44].…”
Section: Clinical Impact Of Adipose Tissue Wasting In Cachexiamentioning
confidence: 99%